Moodle: a program by and for teachers (Journal of Parents and Teachers, 2014)
This article about IT’s explains what moodle is and what it is used for. Moodle is an e-learning platform and a website of course management. It is used to create, distribute, manage debates, give out questionnaires, evaluate and communicate online with students and teachers.
Keywords: IT’s; online tool; services platform; moodle.